The Influence of Economic Growth and Unemployment Rate on Government Expenditure in North Sumatra Province - Sihombing, Isra; Hutasuhut, Khairul Ali (TALENTA PUBLISHER UNIVERSITAS SUMATERA UTARA, 2025)
This study aims to analyze the effect of economic growth and unemployment rate on government expenditure in North Sumatra Province. The research employs a quantitative approach using secondary data in the form of annual time series for the 1990–2024 period, obtained from the Central Bureau of Statistics (BPS) and various scientific literature. Data analysis was conducted using multiple linear regression with the assistance of SPSS version 22. The results show that, partially, economic growth has a negative and significant effect on government expenditure, indicating that an increase in regional economic activity is followed by a decrease in government spending, along with a stronger role of the private sector. Meanwhile, the unemployment rate does not have a significant effect on government expenditure, meaning that unemployment fluctuations are not yet considered a main determinant in regional budget decisions. Simultaneously, both independent variables significantly influence government expenditure in North Sumatra. Thus, overall macroeconomic dynamics play an essential role in shaping regional fiscal policy.